Lanthanide (III) Complexes of Triazene-1-oxides - Sharma, Ramadhar; Thakur, A.K. (Asian Journal of Chemistry, 2010)
Lanthanum(III), cerium(III), praseodymium (III), neodymium (III), samarium(III), gadolinium(III),terbium (III), dysprosium(III)and yttrium(III)complexes of substituted monobasic bidentate triazene-1-oxides (TH) have been synthesized and characterised. The complexes conform to the compositions [LnT3(H2O)n (n = 1, 2). The characterisation of the eighteen newly synthesized complexes of the trivalent lanthanides has been made on the basis of elemental analyses, conductance measurements in dimethylformamide (DMF) at 0.001 M, magnetic moments, infra-red spectra and electronic absorption spectra.